A Chronic Inflammatory Inductive Condition in the Nursing Profession: A Scoping Review - Vitale, Elsa (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Literature focuses on the well-being of patients and little on the wellbeing of nurses who, in turn, should be educated about well-being. On the other hand, the latter often work under serious pressure with inadequate resources and shift organizations, exposing them to health risk factors. Objective: To highlight which relationships exist between diet, physical activity, body mass index (BMI) and mental health in nursing. Methods: The author searched the Medline (PubMed) database for medical subheadings terms and free full text referred to “Diet,” “Mental Health,” “Physical Activity,” and “Nurses” before 31st December 2020. Results: A total of 11 studies were included in this perspective review, which better defined the relationships between diet, physical activity, mental health and the nursing profession. Conclusion: From the studies present in the literature, it emerges that the nursing profession has an inherent imbalance in the regular circadian activity of human nature, as nursing assistance is provided 24 hours a day and during the night. Numerous studies have highlighted significant differences between mental and eating disorder levels among nurses who work at night versus those who only work during the day. Therefore, it is possible to speak of the nursing profession as an “inductive inflammatory-chronic” activity based on the extensive scientific evidence provided by the literature.
Keywords: inflammation